Merokok Sebagai Mekanisme Coping: Strategi Pengelolaan Emosi pada Gen Z - Fahni, Nur (Media Literasi Indonesia, 2026)
Generation Z faces increasingly complex academic, social, and emotional pressures, leading to the adoption of various coping strategies, including smoking behavior. Despite extensive public health campaigns, smoking is still perceived as a quick way to relieve emotional tension. This study aims to explore how Generation Z interprets smoking as a coping mechanism for emotional regulation. A qualitative approach using phenomenological and case study methods was employed. The participants consisted of ten male individuals aged 15–24 years, including nine active smokers and one former smoker. Data were collected through semi-structured in-depth interviews and light observation, then analyzed thematically while ensuring credibility through triangulation and member checking. The findings indicate that academic stress, family conflict, social pressure, anxiety, and boredom are the main triggers for smoking behavior. Smoking is interpreted as emotional escape, calming strategy, personal space (me time), and part of social identity. The emotional process reflects tension before smoking, calmness during smoking, and relief often accompanied by regret afterward. This study concludes that smoking functions as an emotional-focused coping strategy that provides temporary relief but tends to be maladaptive.